(untitled) (Research, Society and Development, 2022)
Investigating the capacity of the solar resource in a given region is the first and most important step in the process of making investments viable and implementing photovoltaic generation systems. The present work aims to visually analyze the main squares of solar energy production in Bahia. For this, a review of the basic concepts, variables involved and works related to the proposed theme was carried out. Furthermore, regional data from Bahia on normal direct irradiation and diffuse irradiation were presented, seeking to assess the contrasts between these locations. As a result of the analysis, there was a finding of the great potential for solar production, respectively, in the mesoregions, microregions and municipalities of the state, with the presentation of the highest and lowest rates of these irradiations. At the end of the work, it was concluded that photovoltaic generation is a good financial investment in Bahian locations, in addition to contributing to the sustainable development of the country, being necessary to identify the best suitable technology for frequent solar irradiation in the place where it will be installed.